Antioxidant, Polyphenol, and Flavonoid Activity Testing of Anchovy Nuggets with Moringa Leaves and Cassava Leaves Substitution - Habsari, Windi; Lestari, Dita; Hartanto, Willcent (Universitas Djuanda, 2025)
Moringa (Moringa oleifera) and cassava leaves (Manihot esculenta) are rich sources of bioactive compounds such as polyphenols, flavonoids, saponins, and tannins, which exhibit significant antioxidant activity. This study aimed to evaluate the antioxidant activity of ethanolic extracts of moringa and cassava leaves using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) method. Results revealed that moringa leaf extract demonstrated weak antioxidant activity with an IC50 value of 699,83±7,3409 ppm, compared to Vitamin E (IC50 4.91 ppm). Moringa and cassava leafs, however, exhibited significant antioxidant activity, particularly in scavenging free radicals, attributed to their polyphenol and flavonoid content. This study highlights the potential of both leaves as natural ingredients for enhancing the antioxidant capacity of food products, although higher concentrations are required to match the effectiveness of synthetic antioxidants.